Anti-methicillin-resistant Staphylococcus aureus (MRSA) activity of Rubiaceae, Fabaceae and Poaceae plants: A search for new sources of useful alternative antibacterials against MRSA infections - Sharifi-Rad, M; Iriti, M; Sharifi-Rad, M; Gibbons, S; Sharifi-Rad, J (Cellular and Molecular Biology, 2016)
In this study, we evaluated the effects of the extracts of the leaves of species from the Rubiaceae (Galium aparine L. and Asperula arvensis L.), Fabaceae (Lathyrus aphaca L. and Vicia narbonensis L.) and Poaceae (Digitaria sanguinalis (L.) Scop. and Hordeum murinum L.) plant families on a wide and extensive panel of isolated methicillin-resistant Staphylococcus aureus strains (MRSA). The effects of the methanolic leaf extracts of Rubiaceae, Fabaceae and Poaceae plants on MRSA were evaluated by the disc diffusion assay and the broth dilution method. Among a total of 177 S. aureus isolates, 92 (51.97%) were found to be methicillin-resistant in an antibiogram and this was confirmed by the presence of the mecA gene in polymerase chain reaction method. All MRSA isolates were sensitive to all extracts. There were dose-dependent inhibitions on tested microorganisms for all plant extracts which showed maximum inhibition zones at a concentration of 300 mg/L. L. aphaca, G. aparine and H. murinum exhibited the highest antibacterial activity on the MRSA strains compared to the positive control (P < 0.05), as well as higher total polyphenol and flavonoid contents than other plant extracts. Minimum inhibitory concentrations on MRSA isolates ranged from 388.4 ± 0.2 mg/L, in D. sanguinalis, to 5.5 ± 0.1 mg/L, in L. aphaca. The methanolic extracts of L. aphaca (Fabaceae), G. aparine (Rubiaceae), and H. murinum (Poaceae) proved to have high antibacterial activity on MRSA isolates, thus representing promising antimicrobial agents in clinical settings.